Assessing Italian wine quality and prices: de gustibus non disputandum est. Issue 5 (3rd May 2016) - Cacchiarelli, Luca; Carbone, Anna; Esti, Marco; Laureti, Tiziana; Sorrentino, Alessandro
Abstract : Purpose: – The purpose of this paper is to focus on high segments of the Italian wine market. The goal is twofold. First, it aims at understanding to what extent wine experts are influenced by specific quality clues. Second, it seeks at assessing the role and effectiveness of different quality clues in the creation of price. Design/methodology/approach: – To meet these goals two independent equations are set. The first – estimated via an ordered logit – explaining the rating of a wine with a bunch of attributes of the wine and of its production process. The second equation is a hedonic price model – estimated via an interval regression – where price is a function of a large number of quality clues. The analysis covers 2, 523 wines from three Italian regions as reviewed by Veronelli Guide, 2010 edition. Findings: – The model estimation results indicates that: few attributes seems to systematically impact experts' judgments; many quality clues are associated with significant price premiums (PP); and in some cases consumers give value to quality clues along with Veronelli's experts while in other cases there is no such alignment. Originality/value: – This study advances the literature in two different ways. First, modeling two distinct equations that describe the factors affecting, on the one side, experts' evaluations, and, on the other side, market prices. Second, as it assesses the PP associated to quality clues whose value has not been considered so far in hedonic price models. The authors affirm that assessing factors that influence experts brings more transparency and a better segmentation in the guide market and in all experts' quality signals.